Sustentabilidade econômica e a utilização de tecnologias digitais nas operações empreendedoras de mulheres idosas - Witt, Andréia Carla Velho (My University, 2024)
The demographic profile continually shows an increase in the life expectancy of the elderly, increasing attention to this population and reiterating the importance of following the new paths that will be offered to people with unique experiences and learning. Given the increase in the life expectancy of elderly people, combined with the importance of them feeling welcomed by society and the need to supplement their income, there is a need to use technology that encourages competitiveness and business efficiency for elderly entrepreneurs. In view of the above, this research aims to present how digital technologies can contribute to the economic sustainability of the entrepreneurial activities of elderly women. To this end, descriptive research was carried out with a qualitative approach. Data were collected through the focus group and examined through content analysis. The focus group was composed of 11 elderly women entrepreneurs, aged between 61 and 70 years old, working in different areas. Through the analysis of interview transcripts, several relevant aspects were identified that characterize the relationship between elderly women, digital technologies and economic sustainability. The main results include greater customer reach, process optimization, improvement of skills and provision of personalized services, which are directly linked to the economic sustainability of elderly women. The study also highlights the importance of combining traditional and modern methods, such as word of mouth and digital technologies, for business success. Digital technologies empower elderly entrepreneurs by modernizing their operations, ensuring the intelligent use of digital tools and maximizing their benefits. These technologies expand market reach and diversify sources of income, complementing pensions and providing greater financial security. Furthermore, these tools contribute to alignment with sustainable development goals and the Decade of Healthy Aging 2020-2030. [resumo fornecido pelo autor]
O perfil demográfico apresenta continuamente o crescimento da expectativa de vida dos idosos, ampliando a atenção a esse público e reiterando a importância de acompanhar os novos caminhos que serão oportunizados para pessoas com vivências e aprendizagens únicas. Diante da ampliação da expectativa de vida do idoso, aliada à importância de o mesmo se sentir acolhido pela sociedade e pela necessidade de complemento de renda, surge a necessidade da utilização de tecnologia que incentiva a competitividade e a eficiência dos negócios para empreendedoras idosas. Diante do exposto, esta pesquisa tem como objetivo apresentar de que forma as tecnologias digitais podem contribuir para a sustentabilidade econômica das operações empreendedoras de idosas. Para tal, foi realizada uma pesquisa descritiva com abordagem qualitativa. Os dados foram coletados por meio de grupo focal e examinados através de análise de conteúdo. O grupo focal foi composto por 11 mulheres empreendedoras idosas, com idades entre 61 e 70 anos, atuando em diferentes áreas. Através da análise das transcrições das entrevistas, foram identificados diversos aspectos relevantes que caracterizam a relação entre idosas, tecnologias digitais e sustentabilidade econômica. Como principais resultados, destaca-se: maior alcance de clientes, otimização de processos, aprimoramento de habilidades e oferta de serviços personalizados, que se interligam diretamente à sustentabilidade econômica das idosas. O estudo também destaca a importância da combinação de métodos tradicionais e modernos, como o "boca a boca" e as tecnologias digitais, para o sucesso dos negócios. As tecnologias digitais fortalecem as empreendedoras idosas, modernizando suas operações, garantindo o uso inteligente das ferramentas digitais e maximizando seus benefícios. Essas tecnologias ampliam o alcance de mercado e diversificam as fontes de renda, complementando as aposentadorias e proporcionando maior segurança financeira. Além disso, essas ferramentas contribuem para o alinhamento aos objetivos de desenvolvimento sustentável e para a Década do Envelhecimento Saudável 2020-2030. [resumo fornecido pelo autor]
Keywords: Empreendedorismo - Idosas; Tecnologia; Sustentabilidade; Entrepreneurship - Older women; Technology; Sustainability